2018
DOI: 10.17765/1983-1870.2018v11n3p467-474
|View full text |Cite
|
Sign up to set email alerts
|

Melhora Do Estilo De Vida Reduz O Índice De Castelli 1 Em Indivíduos Com Síndrome Metabólica

Abstract: Avaliar o efeito de diferentes intervenções para modificação do estilo de vida sobre o Índice de Castelli 1 em indivíduos com síndrome metabólica. Tratou-se de uma subanálise de um ensaio clínico randomizado. Foram incluídos no estudo indivíduos com diagnóstico de síndrome metabólica e idade entre 30 e 59 anos, que foram posteriormente randomizados em três diferentes grupos de intervenção. Foram realizadas avaliações antropométricas e bioquímicas no início do estudo e ao final dos três meses de intervenção. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
1
1
2
Order By: Relevance
“…High Castelli I and II indices indicate a higher cardiovascular risk since these indices often correlate with hypertriglyceridemia, hypertension, glucose intolerance, and insulin resistance [34]. In the present study, only the Castelli II index correlated significantly with the highest tercile of consumption of ultraprocessed foods (median of 35.6% UPF); the odds ratio of presenting this altered index was 2.29 times higher for those adolescents in the highest tercile of consumption of UPF.…”
Section: Discussioncontrasting
confidence: 41%
“…High Castelli I and II indices indicate a higher cardiovascular risk since these indices often correlate with hypertriglyceridemia, hypertension, glucose intolerance, and insulin resistance [34]. In the present study, only the Castelli II index correlated significantly with the highest tercile of consumption of ultraprocessed foods (median of 35.6% UPF); the odds ratio of presenting this altered index was 2.29 times higher for those adolescents in the highest tercile of consumption of UPF.…”
Section: Discussioncontrasting
confidence: 41%
“…O uso dos IC-I e IC-II têm sido descritos na literatura como potencial preditor de RCV e eventos cardiovasculares na população adulta, principalmente na presença de doenças crônicas (Gowda et al, 2019;Feoli et al, 2018;Kamoru et al, 2017).…”
Section: Discussionunclassified
“…The results showed that the experimental groups, that received the intervention (also consisted of the protocol described here), obtained absolute variations and significant percentages, while the standard intervention had unfavorable results (Feoli et al, 2018).…”
mentioning
confidence: 86%